A SOCIO-COGNITIVE STUDY OF THE NOVEL, “WE ARE NOT LIKE THEM”, FROM THE PERSPECTIVE OF RACISM - Zain Fatima; Muhmammad Irfan Ahmad (International Journal of Contemporary Issues in Social Sciences, 2024)
This qualitative research aspires to engage in a socio-cognitive discourse analysis of the novel, “We Are Not Like Them”, from the perspective of racism. It explores the reinforcement and disruption of racial dynamics and prejudices within this compelling narrative. Conceived by Christine Pride and Jo Piazza, the novel, “We Are Not Like Them”, provides a panoramic view of the contemporary American society, delving into the subtle demonstrations of racism in various forms and hues. Focused through a lens of critical race theory, this study is informed by the analytical framework of socio-cognitive discourse analysis. It aims to examine how racial biases, ideologies, and power disparities are constructed and subverted via social cognition and interactions among various characters. Reflecting on micro and macro structures of a society, this research forays into how racism manifests itself within memory as fundamental beliefs and interpersonal relationships. In view of the ultimate goal of establishing an egalitarian society, this analysis attempts to highlight the cross racial challenges, overcome through the mutual bond of love, and selfless friendship between two main characters of the novel. By locating the novel within broad spectrum socio-cultural and ideological contexts, it promotes an ongoing dialogue on race, power dynamics, and identity, urging readers to endorse social justice and equity.